Routledge handbook of humanitarian communication - Chouliaraki, Lilie; Vestergaard, Anne, 1972- (Abingdon ; New York : Routledge, 2021)
The Routledge Handbook of Humanitarian Communication is an authoritative and comprehensive guide to research in the academic sub-field of humanitarian communication. It is broadly focused on communication that presents human vulnerability as a cause for public concern and encompasses communication with respect to humanitarian aid and development as well as human rights and "humanitarian" wars.Recent years have seen the expansion of critical scholarship on humanitarian communication across a range of academic fields, sharing recognition of the centrality of media and communications to our understanding of humanitarianism as an agent of transnational power, global governance and cosmopolitan solidarity. The Handbook brings into dialogue these diverse fields, their theoretical frameworks and methodological approaches as well as the public debates that lie at the heart of the contemporary politics of humanitarianism. It consolidates existing knowledge and maps out this emerging field as an important site of interdisciplinary knowledge production on media, communication and humanitarianism.As such, the Handbook is not simply a collection of texts sharing a similar theme. It is a coherent intellectual contribution which systematizes current critical scholarship in terms of Domains, Methods and Issues and sets an agenda of emerging and evolving research priorities in the field. Consisting of 26 chapters written by international scholars, who have contributed to laying the foundation ofthe field, this volume provides an essential guide to the key ideas, issues, concepts and debates of humanitarian communication.
Keywords: Humanitarian assistance; Communication; Humanitarianism; SOCIAL SCIENCE / General; SOCIAL SCIENCE / Sociology / General